Low-valent Organometallic Derivatives of Palladium(O), Platinum(O) and Rhodium(I) with 4-Amino-5-mercapto-3-substituted-1,2,4-triazoles - PANDEY, R.N.; KUMAR, ASHOK; SINGH, D.P. (Asian Journal of Chemistry, 2010)
Low-valent organometallic derivatives of palladium(O) platinum(O) and rhodium(I) with 4-amino-5-mercapto-3-substituted-1,2,4-trizoles have been isolated from displacement reaction of M(PΦ3)4 (M = Pd/Pt) and Rh(PΦ3)3Cl with methyl and ethyl substitution of ligand in benzene medium. Oxidation state of metals in these compounds are determined iodometrically. Most probable tetrahedral structure of Pd(O), Pt(O) and square planer configuration for Rh(I) have been assigned using various physico-chemical data. Metal ligand vibrations in the far-infrared spectra of complexes have been reasonably assigned.